Hepatobiliary malignancies in Wilson disease - Pfeiffenberger, Jan; Mogler, Carolin; Gotthardt, Daniel; Schulze-Bergkamen, Henning; Schemmer, Peter; Schirmacher, Peter; Stremmel, Wolfgang; Weiss, Karl Heinz (Liver international, 2015)
Backgrounds & Aims Reports of hepatobiliary malignancies in Wilson disease are sparse. The aim of this study was to evaluate hepatobiliary malignancies in Wilson disease patients concerning the clinical course of tumour disease and pathological analysis of tumour tissue. Methods Multicenter cohort study of patients with confirmed diagnosis of Wilson disease treated at the Second Department of Neurology, Institute of Psychiatry and Neurology, Warsaw, Poland, the university hospitals Heidelberg, Duesseldorf and Dresden, Germany, and the Department of Hepatology, University Leuven, Belgium. Occurrence, treatment and outcome of hepatobiliary tumours were analysed retrospectively. Results Of a total of 1186 patients, fourteen developed hepatobiliary malignancies. Eight were hepatocellular carcinomas (HCC) and six were intrahepatic cholangiocellular carcinomas (ICC). The prevalence of hepatobiliary malignancies in the cohort was 1.2% and the incidence was 0.28 per 1000 person years. Pathological analysis of tumour material showed no abnormal copper concentration. Conclusions The rate of hepatobiliary malignancies in Wilson disease is very low, even in cirrhotic patients. As a result of the relevant number of ICC in addition to HCC histological analysis through surgical resection or biopsy should be mandatory when a suspect liver lesion is detected. The influence of copper depletion from Wilson disease-specific medical treatment on tumour activity remains to be elucidated.